Ura knjižničnega informacijskega znanja s QR-kodo v Zavodu za gluhe in naglušne Ljubljana - Janžekovič, Nina (Šolska knjižnica, 2014)
The majority of users of the school library of the Institute for the Deaf and Hearing-Impaired are persons with special needs. The teaching is individualized and adapted to the children's deficits. The classes of Library and Information Knowledge (KIZ) are executed in co-operation with the teachers. The goals are to develop the children's independence in the use of library and its materials, as well as development of positive attitudes towards library space. The paper presents an example of KIZ lesson using QR code. The students searched for QR codes in the library where each code hid a question. The children had to find answers to these questions in a specified book on a specified shelf. In this way they got acquainted with materials arrangement and the UDC system.
Keywords: gluhi; knjižnično informacijsko znanje; naglušni; otroci s posebnimi potrebami; šolske knjižnice; timsko delo